Evidence of chikungunya virus infection among febrile patients in northwest Ethiopia. (March 2021) - Ferede, Getachew; Tiruneh, Moges; Abate, Ebba; Wondimeneh, Yitayih; Gadisa, Endalamaw; Howe, Rawleigh; Aseffa, Abraham; Tessema, Belay
Highlights: Chikungunya virus infection is an unrecognized public health problem in northwest Ethiopia. Increased seroprevalence of chikungunya virus infection was observed during monsoon and post-monsoon periods. The most common clinical presentation observed for chikungunya virus infection was fever, followed by headache and joint pain. Abstract: Background: Chikungunya virus (CHIKV) infection has similar clinical presentations to malaria. Hence, febrile illnesses are often misdiagnosed as malaria. Therefore, this study aimed to generate baseline data on CHIKV infection in northwest Ethiopia where malaria is endemic. Methods: A hospital-based cross-sectional study was conducted among febrile patients presenting at the Metema and Humera Kahsay Abera hospitals from March 2016 to May 2017. Data on socio-demographic, clinical presentations, and possible risk factors were collected using a structured questionnaire. Serum samples were screened for immunoglobulin-M (IgM) and IgG antibodies to CHIKV infections using enzyme-linked immunosorbent assay. Logistic regression analysis was used to determine the strength of association. Results: Of 586 samples screened, the overall seroprevalence of CHIKV infection was 23%. Of the total study participants, 22.5% had CHIKV-specific IgM, indicating recent CHIKV infection. During monsoon and post-monsoon periods, increased prevalence of anti-CHIKV IgM seropositivity was found. The most common clinical presentation observed was fever, followed by headache and joint pain. Men had twice the likelihood of CHIKV infection. The presence of stagnant water near the residence almost doubled the risk for CHIKV infection. Conclusions: Most of the study participants had recent infection with CHIKV, suggesting the need to design disease prevention and intervention strategies.